Oral contraceptive use in Premiership and Championship women's rugby union: perceived symptomology, management strategies, and performance and wellness effects - Heyward, O.; Elliot-Sale, K. J.; Roe, G.; Emmonds, S.; Hornby, K.; Stokes, K. A.; Jones, B. (Science and Medicine in Football, 2024)
The aim of this study was to investigate the prevalence of oral contraceptive use in domestic rugby union, to compare symptomology by contraceptive use, and to determine symptom management strategies. Additionally, to characterise the perceived influence of oral contraceptive use and non-use on wellness and performance. A total of 238 Premiership and Championship women`s rugby union players completed an online questionnaire. The survey was comprised of questions relating to player characteristics, hormonal or non-hormonal contraceptive characteristics, perceived symptomology, symptom management strategies, and performance and wellness characteristics. The prevalence of oral contraceptive users was 26%. Non-hormonal contraceptive users reported greater perceived negative symptomology (i.e., back pain, nausea, sore breasts) and performance and wellness effects (i.e., fatigue, stress, mood, concentration, power, match-play) than oral contraceptive users. The most common symptom management strategies were medication (33%), nutritional interventions (20%), and training modulation (20%). Twelve percent of players had previously spoken to staff about their menstrual cycle (i.e., regular and irregular) or contraceptive use. The most common barriers to speaking to staff were `male staff` (29%) and `club culture` (24%). The importance of assisting non-hormonal contraceptive users in managing symptoms is evident. Emphasis on overcoming barriers to staff-player dialogue regarding menstrual/contraceptive cycle is required.